The Relationship between in Health Gymnastics Participation and Social Integration: A Comparative Study among Secondary School - BOUFRIDA, Abdelmalek; RAFIKA, Cherabcha; JAMEL, Seraiaia (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
This study aims to conduct a comparative investigation of the level of social integration between gymnastics practitioners and non-practitioners among secondary school students in the Wilaya of Guelma, Algeria. The sample consisted of 60 final-year students, equally divided by gender (30 males and 30 females). Each gender group was further divided into 15 practitioners and 15 non-practitioners. The Social Integration Scale was used as the research instrument, comprising 40 items distributed across three dimensions: Peer Relations, Teacher-Student Relations, and Participation in School Activities. The study was conducted during March and April 2024. Data were statistically analyzed using descriptive statistics (mean and standard deviation) and an Independent Samples t-test via SPSS (Version 25), with a significance level set at (α = 0.05). The results revealed statistically significant differences in the level of social integration between gymnastics practitioners and non-practitioners for both male and female students. Practitioners recorded higher scores, reflecting a superior level of social integration compared to their non-practitioner counterparts. Consequently, the study concludes that participation in gymnastics significantly contributes to enhancing students' social integration within the school environment. Article history: Received 2025 October 02; Revised 2025 November 14; Accepted 2025 November 17; Available online 2025 November 20; Available print 2025 November 30